An investigation into how journalists experience economic and political pressures on their ethical decisions at the Nation Media Group in Kenya - Maweu, Jacinta Mwende (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2013)
This study investigates how journalists experience economic and political pressures on their ethical decisions at the Nation Media Group (NMG) conglomerate in Kenya. The study uses qualitative semi- structured interviews to examine how journalists experience these pressures on their professional ethics as they make their daily decisions. Grounded in the critical political economy of the media tradition, the findings of the study indicate that economic and political pressures from advertisers, shareholders' interests, the profit motive and the highly ethnicised political environment in Kenya largely compromise the ethical decisions of journalists. The study draws on the work done by Herman and Chomsky in their 'Propaganda Model' in which they propose 'filters' as the analytical indicators of the forms that political and economic pressures that journalists experience may take. The study explores the ways in which journalists experience these pressures, how they respond to the pressures and the ways in which their responses may compromise their journalism ethics. The findings indicate that aside from the pressures from the primary five filters outlined in the Propaganda Model, ethnicity in Kenyan newsrooms is a key 'filter' that may compromise the ethical decisions of journalists at the NMG. The study therefore argues that there is a need to modify the explanatory power of the Propaganda Model when applying it to the Kenyan context to include ethnicity as a 'sixth filter' that should be understood in relation to the five primary filters. From the findings, it would seem that the government is no longer a major threat to journalists' freedom and responsibility in Kenya. Market forces and ethnicity in newsrooms pose the greatest threat to journalists' freedom and responsibility. The study therefore calls for a revision of the normative framework within which journalists' and media performance in Kenya is assessed. As the study findings show, the prevailing liberal- democratic model ignores the commercial and economic threats the 'free market' poses to journalism ethics as well as ethnicity in newsrooms and only focuses on the media- government relations, treating the government as the major threat to media freedom.
Keywords: Nation Media Group Limited; Journalists -- Kenya; Journalistic ethics -- Kenya; Press and politics -- Kenya; Journalism -- Economic aspects -- Kenya; Journalism -- Political aspects -- Kenya; Mass media -- Political aspects -- Kenya; Mass media -- Economic aspects -- Kenya; Freedom of the press -- Kenya